Emotional Intelligence Drives Employee Performance in Indonesia: Kecerdasan Emosional Mendorong Kinerja Karyawan di Indonesia - Mayyora, Elssya; Sumartik (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to determine the impact of Emotional Intelligence, Self-Efficacy, and Work Stress on Employee Performance at PT. Harapan Sejahtera Karya Utama. Utilizing a quantitative approach, data were collected via questionnaires from 71 randomly sampled employees. Data analysis involved multiple linear regression using SPSS 25. The study found that Emotional Intelligence, Self-Efficacy, and Work Stress significantly affect employee performance (Fcount > Ftable = 6.694 > 3.134, Sig < 0.05 = 0.001). However, only Emotional Intelligence had a significant partial effect. Self-Efficacy and Work Stress did not significantly influence performance. Conducted in 2023 in Sidoarjo, this research used descriptive quantitative methods with 229 employees. The sample was determined using Slovin's formula with a 10% error rate. Data were gathered through Likert-scale questionnaires and observations. The study included validity, reliability tests, and multiple linear regression analysis. Classical assumption tests were conducted. The operational definitions involved Emotional Intelligence, Self-Efficacy, Work Stress as independent variables, and Employee Performance as the dependent variable. Results indicated a significant overall effect of the independent variables on performance, with Emotional Intelligence having a notable individual impact. Limitations include a focus on permanent production employees. Future research should broaden the sample for more comprehensive insights. Highlight: Significant Overall Effect: Combined factors significantly impact employee performance. Partial Impact: Only Emotional Intelligence significantly affects performance. Sample Limitation: Study focused on permanent production employees only. Keywoard: Emotional Intelligence, Self-Efficacy, Work Stress, Employee Performance, Quantitative Research 4o